HUBUNGAN FAKTOR GENETIK, KONSUMSI FAST FOOD, KONSUMSI MINUMAN MANIS, DAN AKTIVITAS FISIK DENGAN GIZI LEBIH PADA REMAJA DI SMK EKONOMIKA DEPOK - Indri Mariyani (2023)
Obesity is a condition of body weight increased due to excessive body fat accumulation. The obesity tendency is related to dietary consumption patterns, genetics and imbalances of body activities. The purpose of this study was to determine the relationship between genetic factor, frequency of fast food consumption, consumption of sugar-sweetened beverages and physical activity with the incidence of overweight in adolescents at SMK Ekonomika Depok. This study used a cross-sectional design with stratified random sampling technique. The sample in this study was 110 students of SMK Ekonomika Depok. Data collected in the form of nutritional status, the history of obesity in parents, frequency of fast food consumption, consumption of sugar-sweetened beverages and physical activity. Bivariate analysis in this study used the spearman rank test. The results of the bivariate test showed that there was a significant relationship between genetic factor and overweight (p=0.031, r=0.206); there was a relationship between consumption of sugar-sweetened beverages and overweight (p=0.000, r=0.615), and there was a relationship between physical activity and overweight (p=0.000, r=-0.402); there was no relationship between fast food consumption and overweight (p=0.836, r=0.20). The conclusion of this study is that there is a relationship between genetic factor, consumption of sugar-sweetened beverages and physical activity with overnutrition but there is no relationship between fast food consumption and overweight in adolescents at SMK Ekonomika Depok.